The Effects of Objective 3D Measures of Facial Shape and Symmetry on Perceptions of Facial Attractiveness - Hatch, Cory D. (J Oral Maxillofac Surg, 2017)
PURPOSE: Meeting patient desires for enhanced facial esthetics requires that providers have standardized and objective methods to measure esthetics. We evaluated the effects of objective 3-dimensional (3D) facial shape and asymmetry measurements derived from 3D facial images on perceptions of facial attractiveness. PATIENT AND METHODS: 3D facial images of 313 adults in Iowa were digitized with 32 landmarks and objective 3D facial measures capturing symmetric and asymmetric components of shape variation, centroid size and fluctuating asymmetry were obtained from the 3D coordinate data using geo-morphometric analyses. Frontal and profile images of study participants were rated for facial attractiveness by ten volunteers (5 females and 5 males) on a 5-point Likert-scale and a visual analogue scale (VAS). Multivariate regression was used to identify the effects of the objective 3D facial measurements on the attractiveness ratings. RESULTS: Several of the objective 3D facial measures had significant effects on attractiveness ratings. Shorter facial heights with protrusive chins, mid-face retrusion, faces with protrusive noses and thin lips, flat mandibular planes with deep labio-mental folds, any cants of the lip commissures and floor of the nose, larger faces overall and increased fluctuating asymmetry were rated as significantly (p<0.001) less attractive. CONCLUSION: Perceptions of facial attractiveness can be explained by specific 3D measures of facial shapes and fluctuating asymmetry, which has important implications for clinical practice and research.